SCLERAL BUCKLING VERSUS VITRECTOMY IN THE MANAGEMENT OF MACULA-OFF PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT: A Comparison of Visual Outcomes. Issue 12 (December 2015) - Wong, Chee Wai; Yeo, Ian Yew San; Loh, Boon Kwang; Wong, Edmund Yick Mun; Wong, Doric Wen Kuan; Ong, Sze Guan; Ang, Chong Lye; Lee, Shu Yen
Abstract : Purpose: To compare visual outcomes between pars plana vitrectomy (PPV) with or without scleral buckling (SB) and SB alone in the management of uncomplicated macula-off primary rhegmatogenous retinal detachment. Methods: Case–control study of 723 patients with uncomplicated macula-off primary rhegmatogenous retinal detachment seen at the Singapore National Eye Centre from 2005 to 2011. The primary outcome measure was the proportion of eyes achieving functional success, defined as logMAR best-corrected visual acuity of ⩽0.3 logMAR at 6 months postoperatively. Multivariable logistic regression analysis was performed adjusting for the following preoperative covariates: age, gender, race, lens status, number of tears found, presence of proliferative vitreoretinopathy, operative procedure, logMAR best-corrected visual acuity, and duration of symptoms. Results: Three hundred and eight eyes underwent SB alone, and 415 eyes underwent PPV ± SB. In the SB group, 133 eyes (43.2%) achieved functional success compared with 116 eyes (28.0%) in the PPV ± SB group. This difference was statistically significant on both univariate ( P < 0.001) and multivariable analyses (OR: 1.51, 95% CI: 1.03–2.21, P = 0.03). Conclusion: Scleral buckling alone may achieve visual outcomes that are at least comparable with PPV ± SB in the management of macula-off primary rhegmatogenous retinal detachment. Abstract : In this case–control study of uncomplicated macula-off rhegmatogenous retinal detachment, we showed that repair with scleral buckle alone was associated with better visual outcome than pars plana vitrectomy with or without scleral buckling.